2014
DOI: 10.1007/s00037-014-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

Short lists for shortest descriptions in short time

Abstract: Is it possible to find a shortest description for a binary string? The well-known answer is "no, Kolmogorov complexity is not computable." Faced with this barrier, one might instead seek a short list of candidates which includes a laconic description. Remarkably such approximations exist. This paper presents an efficient algorithm which generates a polynomial-size list containing an optimal description for a given input string. Along the way, we employ expander graphs and randomness dispersers to obtain an Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…In view of these strongly negative facts, the recent results of Bauwens, Mahklin, Vereshchagin and Zimand [BMVZ13] and Teutsch [Teu14] are surprising. They show that it is possible to effectively construct a short list guaranteed to contain a close-to-optimal program for x.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In view of these strongly negative facts, the recent results of Bauwens, Mahklin, Vereshchagin and Zimand [BMVZ13] and Teutsch [Teu14] are surprising. They show that it is possible to effectively construct a short list guaranteed to contain a close-to-optimal program for x.…”
Section: Introductionmentioning
confidence: 93%
“…More precisely, [BMVZ13] showed that one can compute lists of quadratic size guaranteed to contain a program of x whose length is C(x) + O(1) and that one can compute in polynomialtime a list guaranteed to contain a program whose length is additively within C(x) + O(log n). [Teu14] improved the latter result by reducing the O(log n) term to O(1) (see also [Zim14] for a simpler proof).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Given that the Kolmogorov complexity is not computable, it is natural to ask if given a string x it is posible to construct a short list containing a minimal (+ small overhead) description of x. Bauwens, Mahklin, Vereshchagin and Zimand [1] and Teutsch [5] show that, surprisingly, the answer is YES. Even more, in fact the short list can be computed in polynomial time.…”
Section: Introductionmentioning
confidence: 99%
“…
Bauwens, Mahklin, Vereshchagin and Zimand [1] and Teutsch [5] have shown that given a string x it is possible to construct in polynomial time a list containing a short description of it. We simplify their technique and present a shorter proof of this result.
…”
mentioning
confidence: 99%